Nitrogen/sulphur co-doped porous carbon derived from wasted wet wipes as promising anode material for high performance capacitive potassium-ion storage. (September 2019) - Wang, Lifeng; Li, Sijia; Li, Jianlin; Yan, Su; Zhang, Xinyu; Wei, Denghu; Xing, Zheng; Zhuang, Quanchao; Ju, Zhicheng
Abstract: Hard carbon as a promising anode material for potassium-ion batteries (PIBs) has attracted growing attention due to its unique structural features and expanded interlayer compared to graphite. Nevertheless, the electrochemical performance of hard carbon for PIBs remains unsatisfying, which will drive the researchers to explore new approaches to enhance the specific capacity and rate capability of hard carbon. Herein, we explore a low-cost, facile and environmentally friendly strategy for the synthesis of N/S-codoped porous hard carbon (NSPC) via pyrolyzing the wasted wet wipes. The as-prepared NSPC exhibits superior features for potassium ions storage such as the unique 3D coral-like architecture, high specific surface area (357.68 m 2  g −1 ) expanded interlayer distance (0.38 nm) and synergistic effects of nitrogen and sulphur codoping (N-5.78 at%, S-3.41 at%). Specifically, the NSPC electrode delivers high charge capacity of 285.3 mAh g −1 after 50 cycles at a current density of 50 mA g −1 and an excellent rate capability of 150 mAh g −1 at 1000 mA g −1 . This work can not only provide novel insight toward the application of non-woven fabric textiles wastes, but also unique understanding of the K ions storage mechanism at synergistic effects between different dopants. Graphical abstract: N/S-codoped Hierarchically Porous Carbon (NSPC) was prepared by pyrolyzing the wasted wet wipes. The NSPC demonstrating a high performance capacitive potassium-ion Storage, which can not only provide novel insight toward the application of non-woven fabric textiles wastes, but also unique understanding of the Potassium-ion storage mechanism at synergistic effects between different dopants.Image 1 Highlights: N/S-codoped Hierarchically Porous Carbon (NSPC) was prepared by pyrolyzing the wasted wet wipes. The as-prepared NSPC exhibits superior features for capacitive potassium-ion storage. This work can provide novel insight toward the application of non-woven fabric textiles wastes. Further understanding the synergistic effects of potassium-ion storage mechanism with different dopants.